ВЫБОР СИСТЕМЫ ПОЛЕОРИЕНТИРОВАНИЯ ПРИ ВЕКТОРНОМ УПРАВЛЕНИИ АСИНХРОННЫМИ ДВИГАТЕЛЯМИ - Пересада, С.М.; Ковбаса , С.Н.; Онанко , А.Ю. (Інститут електродинаміки НАН України, Київ, 2014)
Vector control algorithms that based on stator and rotor flux orientation are considered. Criteria for assessing of algorithms properties are developed. The results of theoretical analysis of indirect field oriented algorithms for induction motors are presented. Experimentally substantiated robust properties of stator field oriented systems with respect to rotor resistance variations. References 4, figures 3.